Mothers' response on Kangaroo Mother Care intervention for preterm infants - Bernie Endyami; Rosalina D. Roeslani; Rinawati Rohsiswatmo; Soedjatmiko Soedjatmiko (Indonesian Pediatric Society Publishing House, 2009)
Background The low birth weight still remains the main cause of neonatal deaths. Kangaroo Mother Care (KMC) program can provide a better care for low birth weight newborn infants through skin-to-skin contact. Objective The aim of this study was to assess factors and responses from mothers that would influence the re-introduction and re-implementation of KMC at neonatology ward, Cipto Mangunkusumo Hospital, Jakarta. Methods This was a prospective preliminary study using questionnaires, to mothers oflow birth weight infants who would undergo KMC in neonatal ward. Results Most mothers felt sad, guilty, worried, afraid and not confident when they first saw their babies, thus, they were initially doubtful and afraid in the beginning of KMC. But, after KMC was implemented, most of the mothers found positive effects on mother-infant bonding, maternal affection in love or touch, breastfeeding and mother's confidence in newborn care. Conclusions KMC provides benefits for mothers. Most mothers yield positive response when implementing KMC program to their infants.